Factors Influencing the Adoption of Cloud-based Village Information System: A Technology-Organization-Environment Framework and AHP–TOPSIS Integrated Model - Theresiawati Theresiawati; Tjahjanto Tjahjanto; Yuni Widiastiwi; Hamonangan Kinantan Prabu; Bambang Tri Wahyono; Wan Nor Shuhadah Wan Nik (IAES Indonesian Section, 2023)
Cloud-based service is a key area for growth in Indonesia, but there are still very few villages that have adopted a village information system based on cloud computing. This study investigates the factors influencing OpenSID adoption in cloud computing. The research was informed by the Technological Organizational Environmental (TOE) and combined two multi-criteria decision analysis methods, namely, AHP and TOPSIS to analyze the acceptance of cloud computing-based village information systems, the driving factors for adoption, and the selection of forms of OpenSID. The research focuses on the analysis of four dimensions namely organization, trust, innovation, and vendor. The sub-dimensions of each dimension include the organization (the technological readiness of actors, top management support, and firm size), Trust (security and privacy factors), innovation (compatibility, complexity, trialability, and relative advantage factors), and Vendor (vendor reputation, perceived price, and external support factors). Primary data was collected using a questionnaire and semi-structured interviews with respondents from the village government apparatus in Indramayu.Â The results of the study showed an open-source cloud-based village information system is the most suitable alternative solution for government at the village level in Indramayu, West Java Province.Â The results highlighted that the enablers that are critical for cloud adoption include Technology readiness, trust, technological innovation, and vendor. The barriers that are hindering cloud adoption are infrastructure readiness, understanding the use of cloud computing technology, low technical skills and knowledge, data integration issues, and data security. This research is a reference for developing a village information system based on cloud computing.